A, POLITIK HUKUM TENTANG SYARAT POLITIK HUKUM TENTANG SYARAT USIA PASANGAN CALON KEPALA DAERAH (STUDI: PUTUSAN MAHKAMAH AGUNG NO.23 P/HUM/2024 DAN PUTUSAN MAHKAMAH KONSTITUSI NO.70/PUU-XXII/2024) - Agung Hermansyah (Jurnal Hukum Lex Generalis, 2024)
One of the characteristics of a democratic country is that public positions are filled through an electoral mechanism. In most democratic countries, elections are considered a symbol and a benchmark for democracy itself. In the 1945 Constitution there are 2 (two) electoral regimes, namely: (i) Election of the President and Vice President, DPR RI/Provincial DPRD, City/Regency, and DPD which are elected through general elections (Pemilu) and Election of provincial and district heads. , and cities are democratically elected every 5 (five) years. This research uses normative research methods using literature study materials and secondary data originating from statutory provisions and court decisions. The Supreme Court in Decision Number 23 P/HUM/2024 decided and stated that the nomination age was 30 years for the Governor/Deputy Governor and the nomination age was 25 years for the Regent/Deputy Regent starting from the inauguration of the elected regional head candidate pair. Meanwhile, in Constitutional Court Decision No.70/PUU-XXII/2024, the nomination age is 30 years for the Governor/Deputy Governor and the nomination age is 25 years for the Regent/Deputy Regent starting from the date the regional head candidate pair is determined. Both the Supreme Court Decision and the Constitutional Court Decision are final, binding and erga omnes decisions which both must be obeyed and cannot overrule each other. Differences in views between the Supreme Court and the Constitutional Court have caused legal uncertainty. One of the things that can be considered in the future is that there needs to be some kind of iddah period or cooling off period for changes to election rules. If changes occur during this period, then the changes will only be implemented in the next election contestation. In this way, legal certainty and election rules will be much better maintained. Keywords: Regional Election, Supreme Court Decision, and Constitutional Court Decision.